Comparative Analysis on Water Movability in Pores of Different Reservoir Rocks by Nuclear Magnetic Resonance. Issue 5 (October 2015) - Li, Song; Tang, Dazhen; Xu, Hao; Pan, Zhejun; Huang, Weiqiang; Zhu, Xueguang
Based on nuclear magnetic resonance (NMR) relaxation theory, the mathematical model between T2 value and pore size was proposed. The model results showed that small pores have low T2 values, while large pores have high T2 values. Thus, different reservoir rocks, owing to their diverse pore structures, have different T2 distribution characteristics when water-saturation condition is 100%. NMR experiments with different reservoir rocks under different centrifugal speeds were performed. The comparison of pore structures and water movability in diverse rocks was analyzed based on the NMR experimental results. As centrifugal speed increased, water was progressively expelled from the rocks. There are significant differences in the declining in the water saturation and the area of T2 spectrum per unit volume (ST ) of all the four samples. The water saturation declining in clastic rocks is higher than that of coals. Moreover, both T2 peaks of clastic rocks corresponding to small and large pores successively decreased, while for coals, the peaks with low T2 values were hardly affected, which is consistent with the results of water saturation declining. This is because the low T2 values correspond to the adsorption pores in coal, from which water is hard to drain out, and since coal rocks are dominant by adsorption pores, the water movability of coals is lower than that of clastic rocks.